Chatbots in the Workplace: An Interpretive Phenomenological Study of Workers on the Use of ChatGPT - Nenda Pratiwie S (Ridwan Institute, 2023)
The development of AI technology, such as advanced chatbots, provides many variations of assistance to humans. This research discusses the use of chatbots, particularly ChatGPT, in the workplace based on interviews with three informants. Using interpretive phenomenological methods, the study seeks to find out the experience of using ChatGPT to help complete work tasks. The researcher found that ChatGPT can personalize responses based on user prompts. The speed of providing feedback is the Media Richness Theory's dimension that dominates the results of this study. The superiority of ChatGPT is recognized in terms of its speed in providing feedback when quick resolution of work tasks is needed. However, the research also highlights the weakness of ChatGPT in terms of its limited knowledge storage. Further research is expected to explore experiences related to the use of Chatbot technology with other models to enhance understanding of communication technology industries based on AI.